Cross-sectional study of characteristics of body composition of 24,845 children and adolescents aged 3–17 years in Suzhou - Zhao, Yan; Gong, Jin-xin; Ji, Yi-ting; Zhao, Xiao-yun; He, Lu; Cai, Shi-zhong; Yan, Xiang-ming (BMC pediatrics, 2023)
We aimed to analyze the characteristics of the body composition of children and adolescents aged 3-17 in Suzhou, China. A cross-sectional study between January 2020 and June 2022 using bioelectrical impedance was conducted to determine the fat mass (FM), fat-free mass (FFM), skeletal muscle mass, and protein and mineral contents of 24,845 children aged 3-17 who attended the Department of Child and Adolescent Healthcare, Children's Hospital of Soochow University, China. Measurement data was presented in tables as mean ± SD, and groups were compared using the independent samples t-test. FM and fat-free mass increased with age in both boys and girls. The fat-free mass of girls aged 14-15 decreased after reaching a peak, and that of boys in the same age group was higher than that of the girls (p < 0.05). There were no significant differences in FM between boys and girls younger than 9- and 10-years old. The percentage body fat (PBF) and FM index of girls increased rapidly between 11 and 15 years of age (p < 0.05), and those of boys aged 11-14 were significantly lower (p < 0.05), suggesting that the increase in body mass index (BMI) was mainly contributed by muscle mass (MM) in boys. The body composition of children and adolescents varies according to their age and sex. A misdiagnosis of obesity made on the basis of BMI alone can be avoided if BMI is used in combination with FM index, percentage body fat, and other indexes.